FUNGSI SERTIFIKAT HAK ATAS TANAH SEBAGAI JAMINAN KREDIT PERBANKAN DALAM MEMPERLUAS AKSES MODAL DAN MENDORONG INVESTASI USAHA - Sendi Sanjaya; Gunawan Widjaja (BORJUIS: JURNAL OF ECONOMY, 2025)
This study aims to analyse the function of Land Title Certificates as collateral for bank loans and their role in expanding access to capital and encouraging business investment. Through a literature review, this study identifies that land certificates have legal force that provides certainty for creditors, while also serving as an important instrument for debtors to obtain financing. Land certificates not only serve as proof of legal ownership but also as a means of converting illiquid assets into productive business capital. The use of land certificates as collateral for credit has proven to enhance financial inclusion, promote the development of micro, small, and medium enterprises (MSMEs), and accelerate investment across various sectors of the economy. However, the optimisation of this function depends on policy support, the acceleration of land certification programmes, the integration of land information systems with financial institutions, and the improvement of financial literacy among the public. The results of this study are expected to provide strategic recommendations for the government, banks, and business actors in maximising the role of land certificates as a driver of inclusive and sustainable economic growth.